EVALUATION OF METRIBUZIN IN COMBINATION WITH CLODINAFOP, SULFOSULFURON AND PINOXADEN FOR WEED CONTROL IN WHEAT - A. P. SINGH,; TOSHIBA PANDAGARE,; SHALU ABRAHAM,; D. CHANDRAKAR,; T. CHOWDHURY, (The Bioscan, 2015)
A field experiment was conducted during winter season in two consecutive years 2010-11 and 2011-12 at Indira Gandhi Krishi Vishwavidyalaya, Raipur to test the efficacy of metribuzin alone and in combination with other herbicides for the control of mixed weed flora of wheat crop. Out of a total of ten treatments, four consisted of Clodinafop, Sulfosulfuron ,Metribuzin and Pinoxaden applied as alone, another four consisted of combinations of these and one each of weed free and weedy check. During both the years, minimum weed density was recorded in weed free plots at 28DAS. However, similar weed density was observed in sulfosulfuron and metribuzin treated plots at 60DAS and at harvest where the herbicides were applied @25g and 105g ha-1, respectively. Lowest biomass of weeds was observed in weed free plots at 60DAS, whereas at harvest application of sulfosulfuron and metribuzin (25 and 105g ha-1, respectively) showed their highest efficacy to reduce the biomass of weeds. Hence, above treatment combination was proved best with respect to weed control efficacy i.e.56.84 and 60.8 per cent in two respective years. The data of weed index (00 and 00) also supported the efficacy of above treatment. The data on yield and yield attributing characters showed significance of the combination of sulfosulfuron and metribuzin for getting higher yield over weedy check which was however found statistically comparable with weed free condition. The supremacy of above treatment was proved by increment of grain yield with the tune of 48 and 52 per cent in two consecutive years, respectively. Thus it can be concluded that metribuzin in combination with sulfosulfuron is effective to control mixed weed flora of wheat when applied @25g and 105g ha-1, respectively.